Portfolio Assessment in English Language Classes for Young Learners as an Alternative Assessment Method - Sabirova Gulnoza; Xudoyqulova Feruza (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This thesis explores the effectiveness of portfolio assessment as an alternative evaluation method in young learners’ English classes. In modern education, there is an increasing need for assessment methods that continuously monitor students’ progress beyond traditional tests and examinations. Portfolio assessment enables teachers to evaluate learners’ language skills, creativity, and independent thinking. The thesis analyzes the advantages, practical application, and impact of portfolio assessment on young learners’ motivation in learning English.